THE PEDAGOGICAL NECESSITY OF TEACHING ENGLISH TO PRIMARY GRADE STUDENTS BASED ON INTERACTIVE TEACHING METHODS - Raimova Zuhra Abdurahmon qizi (Bright Mind Publishing, 2026)
This article analyzes the pedagogical and psychological significance of using interactive methods in teaching a foreign language to primary grade students abandoning traditional approaches and using them. The cognitive, concentration skills and motivational factors of young school-age children are studied, and it is scientifically based on why interactive methods increase the effectiveness of language acquisition. The article gives recommendations on practical application of Total Physical Response (TPR), gamification and multimedia.
Keywords: Primary education, interactive methods, English, pedagogical necessity, communicative competence, cognitive development, game technology, motivation.